2015
DOI: 10.1002/fsn3.294
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of raw fresh cashew (Anacardium occidentale L.) kernels from different origin

Abstract: The total dietary fiber, sugar, protein, lipid profile, sodium, and energy contents of 11 raw cashew kernel (Anacardium occidentale L.) samples from India, Brazil, Ivory Coast, Kenya, Mozambique, and Vietnam were determined. Total fat was the major component accounting for 48.3% of the total weight, of which 79.7% were unsaturated FA (fatty acids), 20.1% saturated FA, and 0.2% trans FA. Proteins, with 21.3 g/100 g, were ranked second followed by carbohydrates (20.5 g/100 g). The average sodium content was 144 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
81
7
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 28 publications
21
81
7
5
Order By: Relevance
“…Esta característica le confiere a estas semillas mayor valor comercial, pues el contenido de grasa es una característica altamente deseable en la industria de producción de productos o derivados alimenticios. Se ha reportado que la semilla de marañón contiene 48% de grasa (RICO et al, 2015), sin embargo los valores de grasa encontrados en este estudio están muy por debajo de lo reportado (Tabla 3). Lo anterior puede deberse a múltiples factores, como la variedad del cultivo, las características del suelo, clima, tipo e intensidad de fertilización.…”
Section: Discussionunclassified
“…Esta característica le confiere a estas semillas mayor valor comercial, pues el contenido de grasa es una característica altamente deseable en la industria de producción de productos o derivados alimenticios. Se ha reportado que la semilla de marañón contiene 48% de grasa (RICO et al, 2015), sin embargo los valores de grasa encontrados en este estudio están muy por debajo de lo reportado (Tabla 3). Lo anterior puede deberse a múltiples factores, como la variedad del cultivo, las características del suelo, clima, tipo e intensidad de fertilización.…”
Section: Discussionunclassified
“…Previously, Gozalla et al, (2006), Carvalho et al, (2008Souza et al, (2008) and Rico et al, (2016) According to Lima et al (2004), cashew kernel moisture varies in the range of 2.0 to 3.2%. This range is lower compared to our finding (5.19-5.28%) which in its turn is lower than 7.50 and 8.6% reported by Ferrã o (1995) and (Aroyeun, 2009) respectively.…”
Section: Powdery Mildew Effect On Nutritional Qualities Of Cashew Kermentioning
confidence: 96%
“…Aroyeun, (2009), found the percentage of carbohydrates in cashew kernels as 22.84. Later, Rico et al, (2016) reported a mean of 20.5%. Both authors had slightly lower values than our results.…”
Section: Powdery Mildew Effect On Nutritional Qualities Of Cashew Kermentioning
confidence: 98%
“…Hochst. [23,24] and a commercial fruit crop, cashew nuts, Anacardium occidentale L. [25]. In terms of mineral content, the mesocarp and seed tissues of S. rautanenii are excellent sources of essential minerals such as phosphorus, magnesium, potassium, iron, sodium, copper, zinc and calcium [10].…”
Section: S Rautanenii Constitute An Essential Food Cropmentioning
confidence: 99%
“…In terms of mineral content, the mesocarp and seed tissues of S. rautanenii are excellent sources of essential minerals such as phosphorus, magnesium, potassium, iron, sodium, copper, zinc and calcium [10]. Several amino acids and fatty acids (Table 2) have been identified from the mesocarp and seed tissues of S. rautanenii [10,17,[23][24][25][26][27][28]. Compared to conventional nut and oil crops such as A. occidentale, S. rautanenii is a rich source of macro-and micronutrients (Tables 1 and 2).…”
Section: S Rautanenii Constitute An Essential Food Cropmentioning
confidence: 99%